Determination of land restoration potentials in the semi-arid areas of Chad using systematic monitoring and mapping techniques - Takoutsing, Bertin; Winowiecki, Leigh Ann; Bargués-Tobella, Aida; Vågen, Tor-Gunnar (Agroforestry systems, 2023)
The restoration of degraded lands has received increased attention in recent years and many commitments have been made as part of global and regional restoration initiatives. Well-informed policy decisions that support land restoration, require spatially explicit information on restoration potentials to guide the design and implementation of restoration interventions in the context of limited resources. This study assessed ecosystems indicators of land degradation using a systematic approach that combines field surveys and remote sensing data into a set of multi-criteria analyses to map restoration potentials in the semi-arid areas. The indicators considered were soil organic carbon, erosion prevalence, enhanced vegetation index, Normalized differences water index and the Net Primary productivity. Three classes of restoration potential were established: (1) areas not in need of immediate restoration due low degradation status, (2) areas with high potential for restoration with moderate efforts required and (3) areas in critical need of restoration and require high level of efforts. Of the total area of the study site estimated at 88,344 km 2 , 59,146.12 km 2 , or 66.94% of the theoretically recoverable area, was considered suitable for restoration, of which 38% required moderate efforts while 28% require less efforts. The recoverable areas suitable for restoration could be restored through tree planting, soil and water conservation practices, farmers managed natural regeneration, and integrated soil fertility management. These results can help to spatially identify suitable multifunctional restoration and regeneration hotspots as an efficient way to prioritize restoration interventions in the context of limited resources.